The Effects of Advertising Spending and Event Sponsorship on Brand Equity in the Ethiopian Brewery Industry - Salelaw; Tibebe, Gashaw; Singh, Amanpreet (British Journal of Marketing Studies, 2015)
The field of branding and brand equity is new area of research in Ethiopia. The study adapts an exploratory approach to measure the effects of advertising spending and event sponsorship effect on consumer-based brand equity because there is no study conducted in the Ethiopia beer market. Accordingly, the study assumes advertising spending and event sponsorships affecting brand equity dimensions positively. Hence, a conceptual model has been built and structural equation modeling (SEM) is used to verify the model. A quantitative research was undertaken and a cross-sectional descriptive survey research design in nature was applied in the study. The study confirmed that from advertising spending intensity: television advertising spending has a positive effect on brand awareness; and outdoor advertising has a positive effect on brand awareness, brand association, and perceived quality. On the contrary radio advertising has a negative effect on perceived quality, and print advertising has a negative effect on brand awareness. Furthermore, event sponsorship has a positive effect on brand awareness and brand associations.